Volume 1B, Symposia: Fluid Machinery; Fluid-Structure Interaction and Flow-Induced Noise in Industrial Applications; Flow Appli 2014
DOI: 10.1115/fedsm2014-22058
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scale Simulation of Reactive Flow Through a Fixed Bed of Catalyst Particles

Abstract: We investigate the reactive flow through a fixed bed of catalyst particles. Our simulation method belongs to the class of multi-scale approaches and combines nano scale DFT (Density Functional Theory) computations, mean-field kinetics at the micro scale and fully-resolved hydrodynamic simulations at the millimetric scale. At this stage, the simulations at the chemical (nano and micro) scales provide the rate constants needed by the hydrodynamic model in a one-way coupling. In this paper, we focus on the fully-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This is an extension of the work presented in Dorai et al 13 PRS has been shown to be easily extended to heat and mass transfer as the technique used to solve the momentum equations with solid obstacles, as, e.g., Immersed Boundary, Distributed Lagrange Multiplier/Fictitious Domain or lattice-Boltzmann, can be similarly used to solve other conservation equations. [34][35][36][37] An integrated framework based on DEM and PRS for reactive flows, as demonstrated by Partopour et al 34 and other groups, is currently at the final stage of development in our group 5 and will enable us to assess the chemical efficiency uncertainty induced by the multiple input parameters: loading procedure, particle shape, contact force parameters, dimensionless momentum transfer numbers (Reynolds number), dimensionless mass transfer numbers (fluid/solid diffusivity ratio, Schmidt number, Damkohler number) and kinetic models.…”
Section: Resultsmentioning
confidence: 99%
“…This is an extension of the work presented in Dorai et al 13 PRS has been shown to be easily extended to heat and mass transfer as the technique used to solve the momentum equations with solid obstacles, as, e.g., Immersed Boundary, Distributed Lagrange Multiplier/Fictitious Domain or lattice-Boltzmann, can be similarly used to solve other conservation equations. [34][35][36][37] An integrated framework based on DEM and PRS for reactive flows, as demonstrated by Partopour et al 34 and other groups, is currently at the final stage of development in our group 5 and will enable us to assess the chemical efficiency uncertainty induced by the multiple input parameters: loading procedure, particle shape, contact force parameters, dimensionless momentum transfer numbers (Reynolds number), dimensionless mass transfer numbers (fluid/solid diffusivity ratio, Schmidt number, Damkohler number) and kinetic models.…”
Section: Resultsmentioning
confidence: 99%